Stasis and flux: A genomic study of 20,000 years of European prehistory. - Breslin, Emily (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2023)
This thesis presents whole-genome shotgun sequencing data from 79 ancient humans, spanning 20,000 years of European prehistory, from the Upper Palaeolithic to the Iron Age. The aim of this research was to fill in missing gaps in the palaeogenomic record, and to examine the demographic changes which acted on ancient populations at major transition points in prehistory. Chapter One explores the genetic makeup of the Upper Palaeolithic in the south of France through the analysis of three individuals associated with the Magdalenian and Azilian material cultures. The results reveal that the three known genetic clusters of post-glacial hunter-gatherers in western Europe are represented in this small region, and suggest multiple admixture events between populations carrying these distinct strands of ancestry in the post-glacial period. Chapter Two details a 3,000 year time transect of Portuguese prehistory from 56 ancient genomes spanning the Middle Neolithic to the Iron Age. Kinship analysis uncovers an extensive kinship network within a Bronze Age site, and gives insight into the social structure of populations in this time period. Allele- and haplotype-sharing methods uncover the demographic patterns of these populations, and show a clear pattern of population continuity in the region, even during considerable upheavals caused by the Neolithic and Bronze Age migrations. Chapter Three characterises two highly unusual Iron Age sites in Italy, connected to the enigmatic Villanovan culture: the Monumental Complex in Tarquinia, and the necropoli of Fermo, Marche. Analyses of these individuals shows an extensive kinship network in an established, stable population in Fermo, and explores the possible origins of the enigmatic burials of Tarquinia. An evaluation of population continuity between these individuals and modern Italian populations finds signals of population continuity from the Iron Age to modern times.
APPROVED
Keywords: aDNA; population genetics; genetics; genomics; archaeogenomics; palaeogenomics; ancient DNA